Conflito e patrimonialização: o processo de tombamento do Encontro das Águas dos rios Negro e Solimões - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The Encontro das Águas, formed by the encounter of the Negro and Solimões Rivers, located between the counties of Manaus / AM, Iranduba / AM and Careiro da Várzea / AM, besides being a natural landscape of singular beauty that, according to the tourism agents is the most visited spot in Amazonas, it has deep importance in multiple sociocultural processes in the Amazon. For the surrounding residents of the said landscape, the place has other meanings, since the fishing, the agriculture and the tourism form essential elements for their subsistence. However, these people are about to see their source of life bothered by a reinforced concrete structure and the intensification of the circulation of ships, containers and trucks. This work analyzes the conflict that arises when the residents of the neighborhood Colônia Antônio Aleixo take notice of the project of TPL and mobilize to prevent its construction, which unfolded the tipping of the landscape on canvas at the end of 2010 by the National Historical and Artistic Heritage Institute. It is a reflection about the impacts of the interventions of private companies in articulation with managers of public policies on that region and the way in which social agents stand in front in defense of their spaces of collective use, triggering the legislation that establishes the processes of tipping cultural assets in Brazil as a weapon of struggle.
Keywords: Patrimonialização; Conflitos socioambientais; Encontro das Águas; Mobilização; Patrimonialization; Socio-environmental conflict; Mobilization; CIÊNCIAS HUMANAS: ANTROPOLOGIA